Mentalizing During Social Interaction: The Development and Validation of the Interactive Mentalizing Questionnaire - Wu, Haiyan; Fung, Bowen J.; Mobbs, Dean (Frontiers in Psychology, 2022)
Studies have shown that during social interaction a shared system underlies inferring one’s own mental state, and the mental states of others – processes often referred to as mentalization. However, no validated assessment has been developed to measure second order mentalization (one’s beliefs about how transparent one’s thoughts are to others), or whether this capacity plays a significant role in social interaction. The current work presents an interactive mentalization theory, which divides these directional and second order aspects of mentalization, and investigates whether these constructs are measurable, stable, and meaningful in social interactions. We developed a 20-item, self-report interactive mentalization questionnaire (IMQ) in order to assess the different sub-components of mentalization: self-self, self-other, and other-self mentalization (Study 1). We then tested this scale on a large, online sample, and report convergent and discriminant validity in the form of correlations with other measures (Study 2), as well as correlations with online social deception behaviors in real interaction with Mturk studies (Study 3 and Study 4). These results validate the IMQ, and support the idea that these three factors can predict mentalization in online social interaction.